Association Between Serum Lipid Levels, Resilience, and Self-Esteem in Japanese Adolescents: Results From A-CHILD Study - Doi, Satomi; Isumi, Aya; Fujiwara, Takeo (Frontiers in Psychology, 2021)
Previous studies have found that serum lipid levels independently associate with mental health problems in adulthood. However, little is known about the association between serum lipid levels and positive aspects of mental health such as resilience and self-esteem, which develop in adolescence. The aim of this study is to examine the association between serum lipid levels and resilience and self-esteem in Japanese adolescents. Data were pooled data from the Adachi Child Health Impact of Living Difficulty (A-CHILD) study in 2016 and 2018, a school-based, cross-sectional study in Adachi City, Tokyo, Japan (N=1,056, aged 13-14 years). Resilience of the child was assessed by caregivers, and self-esteem was self-identified via questionnaires. Serum lipid levels (total cholesterol, low-density lipoproteins (LDL), and high-density lipoproteins (HDL)) were assessed in school health checkup, in addition to height and weight measurements. Multiple linear regression was applied to investigate the association between standardized serum lipid levels and resilience and self-esteem. LDL showed inverse association with resilience (β=−1.26, 95%CI=−2.39 to −0.14) after adjusting for child’s BMI, month of birth, sex, absence of parent, household income, caregiver’s mental health, lifestyle (e.g., habits of eating, physical activity, and sleep). We also found an inverse association of total cholesterol and higher LDL cholesterol with self-esteem (β=−0.58, 95%C= −0.99 to −0.18; β=−0.42, 95%CI=−0.83 to −0.01, respectively). HDL cholesterol was not associated with resilience and self-esteem. Among Japanese adolescent, total and LDL cholesterol may be biomarkers of resilience and self-esteem.